Mentoring Resident Scholarly Activity: A Toolkit and Guide for Program Directors, Research Directors and Faculty Mentors - Kimberly Fenton; Jiyeon Kim; Erika Abramson; Linda Waggoner-Fountain; Monique Naifeh; Su-Ting Li (Association of American Medical Colleges, 2015)
Abstract Introduction The Accreditation Council for Graduate Medical Education states that "residents should participate in scholarly activity" but provides little guidance for programs on how to best meet these requirements. To successfully have residents participate in scholarly activity requires strong faculty mentoring, which, for research, requires a specific set of skills. For programs interested in developing or enhancing a research program, this toolkit guides program directors as to key considerations for developing a research program, and provides resources they can give to faculty to help build strong mentoring relationships. For faculty, we provide resources to facilitate the mentoring process, such as how to navigate an institutional review board (IRB), where to look for research funding, and how to help trainees ensure they remain on track with their research progress. Methods This toolkit was created by the authors in response to concerns (both from faculty in their individual institutions and in discussions at national meetings) about a lack of resources available to guide program directors and faculty in mentoring trainees in scholarly activity. The authors shared practices from their own institutions, working together to compile resources and address gaps in available materials. These materials have subsequently been implemented at five institutions through various methods which include: direct dissemination to faculty mentors either electronically or by hard copy in person, discussion of contents at faculty meetings, and new resident orientation. Results Qualitative feedback has been obtained by informally surveying program directors, research directors and faculty mentors at six institutions. Survey results are uniformly positive. Program directors and research directors reported that the materials allowed their programs to better clarify requirements for resident scholarship in their programs and enabled them to help guide faculty in their roles as mentors. A subset of faculty and their individual resident mentees would agree that using this material has been useful in framing realistic expectations for a trainee research project, creating better focus questions for the IRB process, and developing timelines for completion of work. Discussion Both residents and faculty found helpful to have concrete, mutually agreed upon expectations as specified in the worksheets of this toolkit. Putting it in writing strengthens the mentor-mentee relationship. In general, junior faculty and those with less experience mentoring residents have found the toolkit contents to be more useful than more senior faculty.